Studying the effects characteristics of earthquakes on the response of dual reinforced concrete structures in relation to their damping coefficient - ديوب, جعفر; عصام ناصر (Latakia University Journal -Engineering Sciences Series, 2023)
In this research, the behavior of two models of reinforced concrete buildings was studied, their structural system is a dual system (shear walls + frames) using two types of dynamic analysis (linear and non-linear) and the effect of changing the damping coefficient was studied, whose values ranged as follows (4%-5%-7%) on the seismic response values (base shear – Natural period – Damping period - maximum displacement story – story drift – story drift ratio - stresses) by the effect of several different real seismic records in dynamic properties and The results were that with the increase of the damping coefficient, the Damping period increases, while the rest of the response values referred to above have been shown that when the damping coefficient increases, these values decrease, except for the Natural period, it was found that there is no relationship with the damping coefficient, and it was also found that the different characteristics of earthquakes used in the research have an acceptable effect on the response values in logical proportions, as it was noted that there is a difference in the response values between the results of linear and nonlinear analysis, and this is logical.